Revision of the Neotropical genus Domodon Reemer (Diptera: Syrphidae), with description of three new species - Carvalho-Filho, Fernando Da Silva; Martins, Marlúcia Bonifácio; de Souza, Matheus Tavares; Reemer, Menno (Zootaxa, 2019)
The Syrphidae genus Domodon Reemer, 2013 so far included two species, D. zodiacus Reemer, 2013 and D. peperpotensis Reemer, 2014, both recorded only from Suriname. Additional specimens belonging to this genus have been collected in many other localities in South and Central America. In this paper, the genus is revised and three new species are described: D. caxiuana sp. nov. (northern South America), D. inaculeatus sp. nov. (northern South America), and D. sensibilis sp. nov. (Costa Rica). The distribution of D. peperpotensis is extended to include French Guiana. Photographs of the type material of the new species and illustrations of male genitalia of all species are provided, as well as a key to species.